A multi-national report on stereotactic body radiotherapy for oligometastases: Patient selection and follow-up* - Dagan, Roi; Lohr, Frank (Acta oncologica, 2016)
Aims Stereotactic body radiotherapy (SBRT) for oligometastases is increasingly used with few evidenced-based guidelines. We conducted a survey to determine patient selection and follow-up practice patterns.Materials and methods Seven institutions from US, Canada, Europe, and Australia that recommend SBRT for oligometastases participated in a 72-item survey. Levels of agreement were categorized as strong (6-7 common responses), moderate (4-5), low (2-3), or no agreement.Results There was strong agreement for recommending SBRT for eradication of all detectable oligometastases with most members limiting the number of metastases to five (range 2-5) and three within a single organ (range 2-5). There was moderate agreement for recommending SBRT as consolidative therapy after systemic therapy. There was strong agreement for requiring adequate performance status and no concurrent chemotherapy. Additional areas of strong agreement included staging evaluations, primary diagnosis, target sites, and follow-up recommendations. Several differences emerged, including the use of SBRT for sarcoma oligometastases, treatment response evaluation, and which imaging should be performed during follow-up.Conclusion Significant commonalities and variations exist for patient selection and follow-up recommendations for SBRT for oligometastases. Information from this survey may serve to help clarify the current landscape.